Enhancing Public Trust Through E-WOM In Islamic Boarding Schools: a Cyber Public Relations Perspective - Ahmad Khotib; M. Imam Khaudli; Andi Setiawan; Budi Santoso; Denis Bahari (Yayasan Darusssalam Bengkulu, 2026)
This study aims to analyze the role of Electronic Word of Mouth (E-WOM) in enhancing public trust in Islamic boarding schools from the perspective of Cyber Public Relations (CPR) at Darussalam Islamic Boarding School Banyuwangi. This research employed a qualitative approach using a case study design. Data were collected through in-depth interviews, participant observation, and documentation involving pesantren administrators, students, alumni, and members of the community. The data were analyzed using thematic analysis and validated through data triangulation. The findings reveal that public trust is strengthened through integrated digital communication strategies, including the optimization of websites and social media, dissemination of value-based educational content, and interactive communication characterized by responsiveness and transparency. Educational content such as religious advice, santri memorization activities, and Shahih Bukhari study sessions contributed to strengthening the pesantren’s reputation and encouraging positive E-WOM. This study implies that Cyber Public Relations serves as an effective strategy for maintaining institutional reputation and strengthening public trust in the digital era.